2022
DOI: 10.1002/dad2.12346
|View full text |Cite
|
Sign up to set email alerts
|

Higher baseline levels of CSF inflammation increase risk of incident mild cognitive impairment and Alzheimer's disease dementia

Abstract: Introduction Few studies have investigated how neuroinflammation early in the disease course may affect Alzheimer's disease (AD) progression over time despite evidence that neuroinflammation is associated with AD. Methods Research participants with cerebrospinal fluid (CSF) biomarkers from the Alzheimer's Disease Neuroimaging Initiative (ADNI) were included in this study. Cox models were used to investigate whether baseline CSF neuroinflammation was associated with inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…C-reactive protein, an indicator of systemic inflammation, was significantly lower in those who regularly took glucosamine, according to data from the National Health and Nutrition Examination Survey (NHANES) [8]. Animal studies also showed that glucosamine might suppress neuroinflammation [75], which is proved to increase the risk of dementia [76]. Furthermore, a prior research discovered that glucosamine might simulate a low-carbohydrate diet in mice through lowering glycolysis and enhancing amino acid catabolism [77]: consequently, glucosamine has been considered a mimicking agent for energy restriction [21].…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein, an indicator of systemic inflammation, was significantly lower in those who regularly took glucosamine, according to data from the National Health and Nutrition Examination Survey (NHANES) [8]. Animal studies also showed that glucosamine might suppress neuroinflammation [75], which is proved to increase the risk of dementia [76]. Furthermore, a prior research discovered that glucosamine might simulate a low-carbohydrate diet in mice through lowering glycolysis and enhancing amino acid catabolism [77]: consequently, glucosamine has been considered a mimicking agent for energy restriction [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that air pollution has a greater negative impact on cognition in females (Kim et al, 2019). In a rat model of AD, exposure to traffic-related air pollution induced earlier and more profound amyloid pathology in females compared with males (Patten et al, 2021) Inflammation Data from a longitudinal study with >38,000 individuals found that APOE-ε4 carriers and females with higher CSF TNF-α, IL-9, and IL-12p40 levels were at the highest risk of progression to MCI/AD (Contreras et al, 2022).…”
Section: Air Pollutionmentioning
confidence: 99%
“…Other markers of neuroinflammation have been associated with AD pathogenesis in recent studies. CSF IL‐12p40, TNF‐α, and IL‐9, biomarkers involved in the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NFκB) pathway that transcriptionally regulates many genes involved in immune response, were associated with clinical progression to MCI or AD 183 . CSF progranulin acted in a protective manner.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…The detrimental effects of neuroinflammation appear to be exacerbated by various other factors such as sex, APOE status, and cerebrovascular disease. Female APOE ε4 allele carriers with high levels of CSF IL‐12p40, TNF‐α, and IL‐9 had the greatest risk of progression, 183 and higher levels of CSF sTNFR2 were associated with worse cognition, mediated by CSF p‐tau181, in women but not men 185 . Higher levels of eight proinflammatory CSF biomarkers combined with lower levels of cerebrovascular disease, measured by pulse pressure, were associated with higher levels of CSF Aβ42 in CU ADNI participants 186 .…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%